2018
DOI: 10.1111/jvim.15346
|View full text |Cite
|
Sign up to set email alerts
|

Focal epilepsy with fear‐related behavior as primary presentation in Boerboel dogs

Abstract: Background Focal seizures with fear as a primary ictal manifestation, their diagnostic challenges, and impact on quality of life are well described in human medicine. Reports focusing on ictal fear‐like behavior in animals are scarce. Objective To describe the clinical and histopathological characteristics of a novel focal epilepsy in Boerboel dogs. Animals Five client‐owned Boerboel littermates presented for evaluation of sudden episodes of severe fear‐related behavior. Methods Clinical examination, complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…In the published literature for canine epilepsy, there are many identified genes that regulate myoclonic epilepsy [ 2 ], and focal seizures associated with fear or aggression have also been considered hereditary in certain dog breeds, with suspected risk variants uncovered [ 27 , 28 ]. Only for the Lagotto Romagnolo [ 10 ] and the Rhodesian ridgeback [ 11 ] has a single gene influencing IE been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In the published literature for canine epilepsy, there are many identified genes that regulate myoclonic epilepsy [ 2 ], and focal seizures associated with fear or aggression have also been considered hereditary in certain dog breeds, with suspected risk variants uncovered [ 27 , 28 ]. Only for the Lagotto Romagnolo [ 10 ] and the Rhodesian ridgeback [ 11 ] has a single gene influencing IE been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study of abnormal behaviour in bull terriers [30], Dodman et al found that tail chasing, irrational fear, and unprovoked aggression were associated with abnormal electro-encephalogram results. In a short case series, Stassen et al identified paroxysmal episodes of acute fear and autonomic signs associated with focal seizures in Boerboel dogs with an onset of signs of three months [31]. In a survey of Groenendael and Tervueren dogs, 77.6% of those with epilepsy had focal seizures.…”
mentioning
confidence: 99%
“…Although most dogs included in the study showed generalised seizures, epilepsy can have different phenotypes, which may often be atypical, such as behavioural disorders, focal twitching, or brief loss of consciousness [4,23,24]. In a clinical setting, these episodes are often diagnosed as compulsiveobsessive or other behavioural disorders, and their differentiation, as well as con rmation of an epileptic background is made possible by EEG examination, which additionally allows us to localise the discharges.…”
Section: Discussionmentioning
confidence: 99%